2016
DOI: 10.1002/jlcr.3423
|View full text |Cite
|
Sign up to set email alerts
|

177Lu‐5‐Fluorouracil a potential theranostic radiopharmaceutical: radiosynthesis, quality control, biodistribution, and scintigraphy

Abstract: The aim of this study is to develop (177) Lu-5-Flourouracil as a potential cancer therapeutic radiopharmaceutical. 5-Flourouracil (5-FU) is widely accepted as an anticancer drug of broad spectrum fame. The labeling of 5-FU was carried out at different set of experimental conditions using high specific activity of (177) LuCl3 . The optimum conditions for maximum radiochemical yield was set: 5-FU (5 mg), (177) LuCl3 (185 MBq), diethylenetriaminepentaacetic acid (10 µg), reaction volume (2 mL), pH (5.5), temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…In our investigations, 50% of the administrated radioactivity was filtered from the kidneys within 10 min, the overall GFR value remained low, that is, 28.13 ml/min which is a 50% slower filtration rate than reported for healthy subjects (60–120 ml/min) . The gold standard 99m Tc‐DTPA under similar conditions showed GFR of 72 ml/min . This value showed the tracer may impose renal toxicity but in case of radiodiagnostic studies, the tracer is used in nano‐molar concentration which precludes the chance of acute toxicity.…”
Section: Discussionmentioning
confidence: 44%
“…In our investigations, 50% of the administrated radioactivity was filtered from the kidneys within 10 min, the overall GFR value remained low, that is, 28.13 ml/min which is a 50% slower filtration rate than reported for healthy subjects (60–120 ml/min) . The gold standard 99m Tc‐DTPA under similar conditions showed GFR of 72 ml/min . This value showed the tracer may impose renal toxicity but in case of radiodiagnostic studies, the tracer is used in nano‐molar concentration which precludes the chance of acute toxicity.…”
Section: Discussionmentioning
confidence: 44%
“…29 The GFR value of gold standard GFR agent ( 99m Tc-DTPA) is 72 mL/min which is small organic molecule and non-proteinous in nature, but due to protein nature of DOTATATE the renal filtration was recorded slow. 7,22 The radiolabeled peptide therapy, however face the renal accumulation in general such as in case of imaging and therapy using radiolabeled minigastrin peptides 29 but in contrast to other radiolabeled peptides 177 Lu-DOTATATE shows rapid renal filtration which is the success point of 177 Lu-DOTATATE therapy. 30 Cytotoxicity study of 177 Lu-DOTATATE kits studied after 21st day of its preparation, by collecting the blood of 177 Lu-DOTATATE administrated animal at Pr-I and Ps-I time points.…”
Section: Discussionmentioning
confidence: 99%
“…1 Gamma or positron emitter radionuclide such as technetium-99m ( 99m Tc), indium-111 ( 111 In), gallium-68 ( 68 Ga) and fluorine-18 ( 18 F) labeled biological molecules are used for imaging process, [2][3][4][5] while beta or alpha emitter radionuclide such as leutitium-177 ( 177 Lu), yttrium-90 ( 90 Y), rhenium-188 ( 188 Re), actinium-225 ( 225 Ac) are used for therapeutic procedures. [6][7][8][9] A variety of radiolabeled regulatory peptides are in clinical trials and few are in clinical practice for imaging and therapy of NETs. NET imaging and therapy bases on peptide-receptor affinity.…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 shows the biodistribution of radio-IodoIrbesartan in different body organs and fluids. All radioactivity levels are expressed as average percent-injected tissue (%ID/ gram ± S.D) [25][26][27][28]. Low thyroid uptake at all times indicated that the of [ 125 I]IodoIrbesartan was relatively stable in vivo [21][22][23][24].…”
Section: Gamma Scintigraphymentioning
confidence: 99%